The Islamist Trend in Egyptian Law - Moustafa, Tamir (Politics and religion, 2010)
The past four decades have witnessed profound transformations in the Egyptian legal system and in the Egyptian legal profession. Article 2 of the Egyptian Constitution now enshrines Islamic jurisprudence as the principle source of law, thus establishing an important symbolic marker at the heart of the state and opening avenues for Islamist activists to press litigation campaigns in the courts. Additionally, the Islamist trend gained prominence within the legal profession, a development that is particularly striking given the long and illustrious history of the Lawyer's Syndicate as a bastion of liberalism. Despite these significant shifts, however, Islamist litigation has achieved only limited legal victories. This article traces the political and socio-economic variables that underlie the Islamist trend in Egyptian law, and examines the impact of Islamist litigation in the Egyptian courts.